Answering a Call to Action on American Workplace and Community Opioid Concerns. (November 2021) - Harnett, Peter; Hindman, John; Duenas, Melissa; Coogan, Michael; Misicko, Heather
Leidos, Inc. is a large government science and technology company. When a Leidos employee lost his son to an opioid overdose, he wrote an impassioned email to the CEO, asking him to take action related to the growing societal problem of opioid use disorders. The CEO understood and accepted this important call to action. Leidos' subsequent efforts included supporting employees and families, as well as community outreach, eventually broadening to include mental health and well-being. This paper outlines the company's efforts to combat opioid use disorders, understanding that they sit within a larger total worker health umbrella inclusive of mental health and well-being. The hope is that this ongoing journey and its exemplars are helpful for other organizations seeking to make an impact for their employees and society.